Penerapan Model Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Media Word Wall dalam Meningkatkan Hasil Belajar - Alamsah, Gina; Sadiah, Ati; Nurdianti, Raden Roro Suci (Global Education Journal, 2023)
The main problem related to this research is the low learning outcomes of students in economics subjects. This study aims to determine whether there is an increase in student learning outcomes before and after treatment as well as differences in increased student learning outcomes in the experimental class with the Teams Games Tournament (TGT) cooperative learning model assisted by Word Wall media and the control class with the conventional model after treatment. The research method used is a quasi-experimental method. Data analysis techniques used the SPSS 25.00 program, namely paired sample t-test and independent sample t-test with a significant level of 5% or 0.05. Based on the research results, the sig. (2-tailed) of 0.000 so that it can be concluded that there are differences in the increase in learning outcomes of students in the experimental class using the cooperative model Teams Games Tournament (TGT) type assisted by Word Wall media after being given treatment with the control class using conventional learning models after completing learning.